COMPARISON OF ANTIBIOTIC SENSITIVITY OF MRSA WITH MSSA AMONG STAPHYLOCOCCUS AUREUS ISOLATES FROM PATIENTS IN THE 48 MILITARY HOSPITAL IN SANA'A CITY, YEMEN - Al-Huraibi, Belques Sharaf; Al-Shehari, Mohammed Mohammed; Al-Moyed, Khaled Abdulkareem; Al-Shami, Huda Zaid; Al-Hymia, Faisal Mohamed; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2023)
Background and objectives: A number of infectious disorders can be opportunistically brought on by Staphylococcus aureus ( S. aureus), which colonizes human skin and mucous membranes. Methicillin (MRSA) resistance is a frequent occurrence, as are resistances to a number of clinically useful antibiotics. Though MRSA affects healthcare systems and society all throughout the world, it is most severe in underdeveloped countries. The Clinical and Laboratory Standards Institute (CLSI) advises that cumulative antibiotic data for S. aureus be analyzed and reported on an annual basis to help clinicians choose the best preliminary empirical antimicrobial therapy. The most recent report from our center on this subject, however, was more than 7 years ago. Subjects and methods: Well-proven S. aureus data were gathered from inpatient and outpatient clinical samples at the 48th Military Hospital, Sana'a, Yemen, from January 1, 2022, through December 2022, using a retrospective cross-sectional design. Using Kirby-Bauer disk diffusion, antimicrobial susceptibility testing (AST) was carried out. Calculations were made on the rate of antibiotic resistance between MRSA and MSSA as well as the correlation between MRSA. Results: Among the 265 unique isolates, the overall prevalence of MRSA was 37.4%. Inpatients had a greater risk factor for MRSA with an OR of 2.7 (p<0.001). A risk factor was also found with the catheter sample, and devices with an OR=3.7 (p=0.003). Methicillin resistance was predictive of resistance to most antibiotics. Zero resistance rate to linezolid, and vancomycin was observed for the MRSA and MSSA strains. The prevalence of multidrug resistant (MDR) isolates was 60.4%. Significantly higher in MRSA (68.7%) versus 55.4% for MSSA. Conclusion: This study's MRSA prevalence was higher than that of earlier research from the same hospital; it is a progressive issue and much below the desired rates. Additionally, there was notable resistance to erythromycin, imipenem, and clindamycin. Vancomycin and linezolid are currently the top two options for the empiric treatment of MRSA. In order to stop the emergence of MDR species, it is suggested against giving newer antibacterial medications while the older ones are still effective. Peer Review History: Received: 5 June 2023; Revised: 9 July; Accepted: 27 August; Available online: 15 September 2023 Academic Editor: Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Reviewers: Dr. Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Tamer Elhabibi, Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg